(untitled) - Desrosier, Norman W. (Westport, connecticut, 1971)
This book introduce the new products and the changing bisiness scene. Managing people and innovation. Merchandising and new products, improving success potential of new products, market exploration and acquisitions...
Keywords: Thương mại và công nghiệp thực phẩm,Food industry and trade; Hoa Kỳ,United States